2011
DOI: 10.1086/662385
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in the Effects of Heat Exposure on Maximum Sprint Speed and Hsp70 Expression in the Western Fence LizardSceloporus occidentalis

Abstract: We examined whether western fence lizards Sceloporus occidentalis occurring in thermally divergent environments display differential responses to high temperature in locomotor performance and heat-shock protein (Hsp) expression. We measured maximum sprint speed in S. occidentalis from four populations at paired latitudes and elevations before and after exposure to an experimental heat treatment and then quantified hind-limb muscle Hsp70 expression. Lizards collected from northern or high-elevation collection s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Several studies have compared the response of HSP60, HSP70 and HSP90 to the ecological factors. While some of the studies found HSP60 is more sensitive than other HSPs (Martínez-Padilla et al 2004;Moreno et al 2005), other studies found HSP70 was more sensitive to environmental perturbations than HSP60 or HSP90 (Ulmasov et al 1992;Fader et al 1994;McMillan et al 2011). Our study showed that HSP70 and HSP90 of nestlings respond to the optimal food condition similarly.…”
Section: Discussionsupporting
confidence: 41%
“…Several studies have compared the response of HSP60, HSP70 and HSP90 to the ecological factors. While some of the studies found HSP60 is more sensitive than other HSPs (Martínez-Padilla et al 2004;Moreno et al 2005), other studies found HSP70 was more sensitive to environmental perturbations than HSP60 or HSP90 (Ulmasov et al 1992;Fader et al 1994;McMillan et al 2011). Our study showed that HSP70 and HSP90 of nestlings respond to the optimal food condition similarly.…”
Section: Discussionsupporting
confidence: 41%
“…Additionally, lizards that experience higher ambient temperatures tend to have higher optimal temperatures for sprinting and these differences do not appear to be attributable to acclimatization alone (Huey and Kingsolver ; McMillan et al. ). Because we did not measure operative temperature (the passive body temperature of a lizard model in the absence of thermoregulation) these data should be considered preliminary with respect to lizard physiology; however, we nonetheless propose that this is an observation that should be investigated by further research.…”
Section: Discussionmentioning
confidence: 99%
“…This change is often coupled with a decrease in locomotor speed and an increase in the frequency of bipedalism (Kohlsdorf and Biewener, 2006). If lizards cannot sprint at (or near) maximum capacity, then their ability to elude predators would be affected (McMillan et al, 2011;De Barros et al, 2010;Okafor, 2010), particularly on uneven substrates containing obstacles. Whereas some studies have examined bipedal locomotion in lizards from a biomechanical standpoint (Hsieh and Lauder, 2004;Kohlsdorf and Biewener, 2006;Olberding et al, 2012;Van Wassenbergh and Aerts, 2013), the present study will examine a mechanistic link between bipedalism and ecologically relevant features of the habitat (obstacles).…”
Section: Introductionmentioning
confidence: 99%